2013
DOI: 10.1007/s11032-013-9854-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the predominant nonrestoring allele for Owen-type cytoplasmic male sterility in sugar beet (Beta vulgaris L.): development of molecular markers for the maintainer genotype

Abstract: Hybrid seed production in sugar beet relies on cytoplasmic male sterility (CMS). As time-consuming and laborious test crosses with a CMS tester are necessary to identify maintainer lines, development of a marker-assisted selection method for the rf gene (the nonrestoring allele of restorer-of-fertility locus) is highly desirable for sugar-beet breeding. To develop such a method, we investigated genetic variation at the Rf1 locus, one of two Rf loci known in sugar beet. After HindIII-digestion, genomic DNAs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 17 publications
2
46
0
Order By: Relevance
“…Our analysis included another transgene made from bvORF20L , the bvORF20 counterpart of rf1rf1 sugar beet lines (Matsuhira et al ., ; Moritani et al ., ). Although levels of transcripts and the translation products of bvORF20L were below the limits of detection by RNA gel blot analysis or immunoblot analysis (Matsuhira et al ., ; and this study), transcription of bvORF20L was indicated by RT‐PCR analysis (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Our analysis included another transgene made from bvORF20L , the bvORF20 counterpart of rf1rf1 sugar beet lines (Matsuhira et al ., ; Moritani et al ., ). Although levels of transcripts and the translation products of bvORF20L were below the limits of detection by RNA gel blot analysis or immunoblot analysis (Matsuhira et al ., ; and this study), transcription of bvORF20L was indicated by RT‐PCR analysis (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…However, 22 of 23 maintainer lines showed the same hybridization pattern. The sequences of the rf1 coding regions of these 22 maintainer lines were found to be identical, confirming that they shared the same rf1 allele (Moritani et al, 2013). Two PCR markers targeting a downstream intergenic sequence and the first intron of Rf1, respectively, were developed.…”
Section: Introductionmentioning
confidence: 75%
“…The PCR protocol was 35 cycles of 94˚C for 3 s , 58˚C for 1 min and 72˚C for 1 min. The DNA fragment used for preparation of the DNA probe was PCR amplified using the primers shown in Moritani et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly used cytoplasm is Owen type originally described in sugar beet as the result of the interaction between a sterilizing cytoplasm and at least two nuclear restorer genes and environmental factors (Owen 1942(Owen , 1945. Restorer gene Rf1 has been cloned and sequenced (Hagihara et al 2005, Matsuhira et al 2012, and molecular markers are available for MAS (Moritani et al 2013). Recently, Honma et al (2014) have reported the molecular mapping of Rf2.…”
Section: Amaranthaceae Subfamily Chenopodioideaementioning
confidence: 99%